Pengembangan Kreativitas dan Keterampilan Siswa dalam Pembuatan Sabun Alami sebagai Produk Wirausaha Siswa SMA Al Wildan Islamic School 2 Bekasi - Hidayat, Ade Nurul; Afra Nuraini; Fitri Nuryani; Ayu Candraningsih; Nur Ilman Ilyas (Jurnal Pelita Pengabdian, 2025)
This activity of devotion to society is carried out by a team of professors of industrial engineering of a former paramadina (upb) university as a form of real contribution in supporting improved education at the middle school level.This program is focused on the development of creative thinking skills and the soul of the entrepreneurship through the approach of project-based learning (project-based learning), which is in effect packed in the form of natural soapmaking training with cold process methods.This method not only introduces basic chemical principles to students, but also encourage understanding of the economic potential of the products they produce., So it's relevant to build entrepreneurial mindsets from an early age..During activity, The teacher's team played an active part in accompanying the 11th grade student high school al wildan islamic school 2 to design, execute, and evaluate the specified project.